Insights into PU/EVA blends produced using industrial residues towards eco-efficient materials - Gama, Nuno (2022)
Aiming at minimizing the issues associated with the disposal of polymers, in this study, elastomeric materials derived from 100% recycled feedstocks were produced. Residues of polyurethane (PU) foams (from 0 to 100%) were blended with residues of ethylene–vinyl acetate (EVA) derived from the shoe-soles industry (from 0 to 100%) to produce films by hot compression. The experimental values obtained by the characterization of the blends were compared with the predicted values derived from the rule of mixtures. Despite of the two-phase morphology observed, the high correlation between the experimental and predicted values suggest that phase segregation did not have a significant effect on the properties of the blends. Voids were also observed on the PU derived materials, due to the source of PU (foams), which reduced their density and increased the water absorption. Yet, this did not jeopardize the mechanical performance of the ensuing materials. In addition, higher amounts of PU resulted in stiffer materials, while higher amounts of EVA induced higher thermal stability. From the results, it was demonstrated that the PU/EVA blends, produced from 100% recycled feedstock, presented suitable properties to be used in shoe-soles applications.